2010
DOI: 10.3354/meps08818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in DMSP content in the invasive seaweed Codium fragile ssp. fragile: effects of temperature, light and grazing

Abstract: The methionine-derived secondary metabolite dimethylsulfoniopropionate (DMSP) is believed to function in cryoprotection, defense against herbivory, and reduction of oxidative stress in some seaweeds. The ability to produce DMSP, and modify its concentration according to environmental conditions, may confer adaptive advantages to these algae. We studied the spatial and temporal distribution of DMSP content in Codium fragile off the Atlantic coast of Nova Scotia. Levels of DMSP in C. fragile were highest in bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…However, the timing of fragmentation and attendant production of detritus by stands of C. fragile varies among regions and occurs throughout the year in some areas (Trowbridge 1996(Trowbridge , 1998. Thalli of C. fragile used for this experiment were collected during the seasonal minimum in DMSP production coincident with high water temperatures (Lyons et al 2010). In regions were fragmentation occurs during periods of low temperature in winter and spring (Fralick & Matheison 1973, Trowbridge 1993, the DMSP content of detrital fragments is likely higher, which may result in a greater deterrent effect on potential consumers and slower degradation rate than observed in our study.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, the timing of fragmentation and attendant production of detritus by stands of C. fragile varies among regions and occurs throughout the year in some areas (Trowbridge 1996(Trowbridge , 1998. Thalli of C. fragile used for this experiment were collected during the seasonal minimum in DMSP production coincident with high water temperatures (Lyons et al 2010). In regions were fragmentation occurs during periods of low temperature in winter and spring (Fralick & Matheison 1973, Trowbridge 1993, the DMSP content of detrital fragments is likely higher, which may result in a greater deterrent effect on potential consumers and slower degradation rate than observed in our study.…”
Section: Discussionmentioning
confidence: 64%
“…We have shown that detached thalli of Saccharina latissima and Codium fragile differ significantly in their rate of degradation, and the manner in which biochemical composition and nutritional quality change during degradation, indicating that displace- Lyons et al 2010) increased slightly in C. fragile 4 wk after transplantation, when mass loss was minimal, likely in response to a decrease in water temperature with depth (Lyons et al 2010). Similarly, the concentration of DMS(P) in attached C. fragile at 5 to 7 m depth (the source of experimental thalli) increased over the course of the experiment from 2.0 to 7.0% (not shown) as temperatures decreased in the shallows from 23 to 7°C.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations